Osteoblast Derived Exosomes Alleviate Radiation- Induced Hematopoietic Injury - Xue, Jianqi; Du, Ruikai; Ling, Shukuan; Song, Jinping; Yuan, Xinxin; Liu, Caizhi; Sun, Weijia; Li, Yuheng; Zhong, Guohui; Wang, Yinbo; Yuan, Guodong; Jin, Xiaoyan; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
As hematopoietic stem cells can differentiate into all hematopoietic lineages, mitigating the damage to hematopoietic stem cells is important for recovery from overdose radiation injury. Cells in bone marrow microenvironment are essential for hematopoietic stem cells maintenance and protection, and many of the paracrine mediators have been discovered in shaping hematopoietic function. Several recent reports support exosomes as effective regulators of hematopoietic stem cells, but the role of osteoblast derived exosomes in hematopoietic stem cells protection is less understood. Here, we investigated that osteoblast derived exosomes could alleviate radiation damage to hematopoietic stem cells. We show that intravenous injection of osteoblast derived exosomes promoted WBC, lymphocyte, monocyte and hematopoietic stem cells recovery after irradiation significantly. By sequencing osteoblast derived exosomes derived miRNAs and verified in vitro, we identified miR-21 is involved in hematopoietic stem cells protection via targeting PDCD4. Collectively, our data demonstrate that osteoblast derived exosomes derived miR-21 is a resultful regulator to radio-protection of hematopoietic stem cells and provide a new strategy for reducing radiation induced hematopoietic injury.